Analisis Prosedur Audit Utang Pada PT ABC oleh Kantor Akuntan Publik Namira - Nuryanto, Nuryanto; Pratiwi, Christa Dian; Bida, Yance; Wardani, Aulia Kusuma; Kurniasari, Isnaini Hijriyah (Universitas Palangka Raya, 2025)
This article aims to analyze the debt audit procedures at PT ABC by public accounting firm Namira where this study discusses the procedures and preparation of third party debt audit work papers at PT ABC by KAP Namira. A company will need the help of a third party, namely an auditor to determine the effectiveness of internal controls and the fairness of the financial statements to be examined. With the help of auditors, evidence on the preparation of the company's financial statements can be examined and evaluated in order to improve the ability to manage funding sources for the sustainability of the company's activities and increase the confidence of users of the financial statements produced by the company. In this case the auditor must examine all the components of the company's financial statements, one of which is on the balance sheet there is an account that must be checked by the auditor, namely debt. The debt arises because the company cooperates with third parties to carry out production activities and borrow funds for the sustainability of the company. Debt itself is a liability component that greatly affects every transaction that occurs, because trade payables are company obligations that must be paid and there are nominal misstatements that are very material for the sustainability of a company. To prevent this from the debt balance, it is necessary to conduct an audit as well as an examination. Based on the final project that the author has compiled, it comes from the internship activities that have been carried out and knows the debt audit procedures implemented by KAP NAMIRA including evaluating internal control evaluations, making top schedules and supporting schedules to sending debt confirmations and also doing vouching.